Issues of Fact-based Information Analysis - Sharonova, Natalia Valeriyevna; Doroshenko, Anastsiia; Cherednichenko, Olga (My University, 2018)
With the recent growth of Internet, mobile and social networks the spread of fake news and click-baits increases drastically. Today, the fact retrieval system is one of the most effective tools for identifying the information for decision-making. We propose the approach based on factual information systematization. Different interpretations of the same phenomenon, as well as the inconsistency, inaccuracy or mismatch in information coming from different sources, lead to the task of factual information extraction. In this work, we explore how can natural language processing methods help to check contradictions and mismatches in facts automatically. The reference model of the factbased analytical system is proposed. It consists of such basic components as Document Search component, Fact retrieval component, Fact Analysis component, Visualization component, and Control component.
Keywords: fact; natural language processing; information extraction; comparator identification; predicate; reference model